Effects of aripiprazole once-monthly on symptoms of schizophrenia in patients switched from oral antipsychotics. (17th August 2016) - Peters-Strickland, Timothy; Zhao, Cathy; Perry, Pamela P.; Eramo, Anna; Salzman, Phyllis M.; McQuade, Robert D.; Johnson, Brian R.; Sanchez, Raymond
Abstract : Objective: To assess the effects of aripiprazole once-monthly 400 mg (AOM 400) on clinical symptoms and global improvement in schizophrenia after switching from an oral antipsychotic. Methods: In a multicenter, open-label, mirror-image, naturalistic study in patients with schizophrenia (>1 year, Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision [DSM-IV-TR] criteria), changes in efficacy measures were assessed during prospective treatment (6 months) with AOM 400 after switching from standard-of-care oral antipsychotics. During prospective treatment, patients were cross-titrated to oral aripiprazole monotherapy (1–4) weeks followed by open-label AOM 400 (24 weeks). Mean change from baseline of the open-label AOM 400 phase in Positive and Negative Syndrome Scale (PANSS) scores (total, positive and negative subscales) and Clinical Global Impression–Severity (CGI-S) scores; mean CGI–Improvement (CGI-I) score; and proportion of responders (≥30% decrease from baseline in PANSS total score or CGI-I score of 1 [very much improved] or 2 [much improved]) were assessed. Results: PANSS and CGI-S scores improved from baseline ( P <0.0001) and CGI-I demonstrated improvement at all time points. By the end of the study, 49.0% of patients were PANSS or CGI-I responders. Conclusions: In a community setting, patients with schizophrenia who were stabilized at baseline and switched to AOM 400 from oral antipsychotics showed clear improvements in clinical symptoms.